2021
DOI: 10.3390/nu13093053
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Adjusted Dietary Intakes Are Associated with Perceived Barriers to Healthy Eating but Not Food Insecurity or Sports Nutrition Knowledge in a Pilot Study of ROTC Cadets

Abstract: Military service is inherently demanding and, due to the nature of these demands, the term “tactical athlete” has been coined to capture the physical requirements of the profession. Reserve Officers’ Training Corps (ROTC) cadets are a unique subset of the military service community, and the complexity of their training and educational pursuits increases their susceptibility to unhealthy eating patterns. The purpose of this pilot study was to explore the relationship between the perceived barriers to healthy ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Nutritional analysis indicated that the cadets were not meeting many of the energy and macronutrient recommendations as per the MDRIs. The mean EI was 2375 ± 620.7 kcal/d, which is similar to a report by Daniels et al who also showed an average EI of 2414 kcal/d in male army ROTC cadets [ 23 ]. This is well below the military’s recommendation of 3400 kcal/d for the average 85 kg male doing moderate levels of activity [ 19 ].…”
Section: Discussionsupporting
confidence: 87%
“…Nutritional analysis indicated that the cadets were not meeting many of the energy and macronutrient recommendations as per the MDRIs. The mean EI was 2375 ± 620.7 kcal/d, which is similar to a report by Daniels et al who also showed an average EI of 2414 kcal/d in male army ROTC cadets [ 23 ]. This is well below the military’s recommendation of 3400 kcal/d for the average 85 kg male doing moderate levels of activity [ 19 ].…”
Section: Discussionsupporting
confidence: 87%
“…Balancing demanding academic and athletic schedules poses a unique challenge for college athletes, often impacting their ability to access adequate nutrition to fuel their sports performance [8,11,12]. Although various factors influence food access for all college students, Nutrients 2024, 16, 1346 2 of 13 recognizing the distinct challenges faced by student-athletes is crucial for developing effective interventions tailored to this specific demographic.…”
Section: Introductionmentioning
confidence: 99%
“…Note: FI = food insecurity; NCAA = National Collegiate Athletics Association; 6-/10-/18-item US-HFSSM = U.S. Household Food Security Survey Module: 6-/10-/18-Item Short Form[16]; NHPI = Native Hawaiian/Pacific Islander.…”
mentioning
confidence: 99%